Sponge Takeover from End-Permian Mass Extinction to Early Induan Time: Records in Central Iran Microbial Buildups - Baud, Aymon; Richoz, Sylvain; Brandner, Rainer; Krystyn, Leopold; Heindel, Katrin; Mohtat, Tayebeh; Mohtat-Aghai, Parvin; Horacek, Micha (Frontiers in Earth Science, 2021)
The end-Permian mass extinction was the most severe biotic crisis in Earth’s history. In its direct aftermath, microbial communities were abundant on shallow-marine shelves around the Tethys. They colonized the space left vacant after the dramatic decline of skeletal metazoans. The presence of sponges and sponge microbial bioherms has largely gone unnoticed due to the sponges’ size and the cryptic method of preservation. In addition to sponge dominated facies recently described in South Armenia and Northwestern Iran, we describe here sponge-microbial bioherms cropping out in two well-known Permian-Triassic boundary localities: the Kuh-e Hambast section, south-east of Abadeh city and the more distal Shahreza section, near Isfahan. In both sections, the extinction horizon is located at the top of an upper Changhsingian ammonoid-rich nodular limestone, called Paratirolites limestone. At Kuh-e Hambast, the overlying decimetric thick shale deposit called “boundary clay,” the latest Permian in age, is conformably overlain by well-dated transgressive basal Triassic platy limestone containing four successive levels of decimeter to meter scale, elongated to form cup-shaped mounds made of branching columnar stromatolites. Sponge fibers from possibly keratose demosponge, are widely present in the lime mudstone matrix. At the Shahreza section, above the extinction level, the boundary clay is much thicker (3 m), with thin platy limestone intervals, and contains two main levels of decimeter to meter scale mounds of digitate microbialite crossing the Permian-Triassic boundary with similar sponge fibers. Three levels rich in thrombolite domes can be seen in the overlying 20 m platy limestone of earliest Triassic age. Sponge fibers and rare spicules are present in their micritic matrix. These sponge fibers and spicules which are abundant in the latest Permian post-extinction boundary clay, followed microbial buildups during the Griesbachian time.